BMP-7/Smad expression in dedifferentiated Schwann cells during axonal regeneration and upregulation of endogenous BMP-7 following administration of PTH (1-34). (14th November 2018) - Kokubu, Naoki; Tsujii, Masaya; Akeda, Koji; Iino, Takahiro; Sudo, Akihiro
Purpose: To determine the expression and distribution of bone morphogenetic protein (BMP)-7 and related molecules during peripheral nerve regeneration and to assess whether administration of parathyroid hormone (PTH) drug (1-34) potentiates the intrinsic upregulation of BMP-7/Smad signaling. Methods: The rat sciatic nerves were crushed with an aneurysm clip resulting in axonal degeneration. In the normal nerve, and at 1, 2, 4, and 8 weeks after injury, BMP-7, BMP receptors, p-Smad 1/5/8, and Noggin, the endogenous BMP antagonist, were evaluated. Additionally, the distribution of BMP-7 was assessed by fluorescent double immunostaining. In vitro studies were also performed to examine the effect of BMP-7 and PTH (1-34) administration on rat Schwann cells (SCs). Results: Aneurysm clip made reliable animal model of the nerve injury with recovery at 8 weeks after the injury. BMP-7/Smad protein and mRNA were significantly upregulated on axon-SCs units at 1 week after injury, and this upregulated expression was maintained for 4 weeks. Besides, significant upregulation of Noggin's expression was observed on axon-SCs units at 2 weeks after injury. Moreover, fluorescent double immunostaining showed co-localization between expression of BMP-7 and p75NTR during axonal regeneration. In the in vitro study, administration of BMP-7 induced significant proliferation of SCs. Application of PTH (1-34) upregulated BMP-7 on SCs. Discussion/conclusion: BMPs were reported to be involved in protection and recovery after injury as well as in neurogenesis. Our current study showed that BMP/Smad signaling molecules were upregulated on dedifferentiated SCs after peripheral nerve injury and that administration of BMP-7 increased SC viability in vitro. These results suggested that axonal regeneration could be induced via upregulation of endogenous BMP-7 on SCs by PTH (1-34) administration.